A governança do conhecimento na coprodução de políticas públicas: estudo de caso do Plano ES – convivência consciente - Dias, Fabrine Schwanz (2023)
In order to understand the Knowledge Governance in the co-production process between organized civil society and the public sector in the development of economic policies in the State of Espírito Santo to address public issues brought about by the coronavirus pandemic, a qualitative and interpretative research was conducted. The data collection instruments included documentary research and episodic interviews with initiative participants. Thematic narrative analysis was employed, enabling the identification of actors and entities involved in this process, their roles and positions, the factors motivating their participation in co-production, and the applied strategies and tools. The conceptual framework of related studies by Van Kerkhoff and Pilbeam (2017) and Audia et al. (2021) was utilized. It became evident that elements influencing the Knowledge Governance operate in a combined manner, forming a uniqueness that characterizes it. Notably, political knowledge plays a prominent role in coordinating other knowledge systems, mediating conflicts, and managing divergent interests. Additionally, considering that the researched civil society entities held distinct economic positions and power relations, the analysis may contribute to enhancing the co-production process of future public policies, fostering greater balance and diversity in their proposal by involved participants, thereby influencing the decision-making process more effectively.